Emerging Trade Battlefield with China: Export Competition and Firm's Coping Strategies - Katariina Nilsson Hakkala; Yao Pan (The Research Institute of the Finnish Economy (ETLA), 2019)
This paper analyzes how intensified Chinese export competition affects the exports and product ranges of firms from Finland. Using a novel identification strategy that exploits changes in Chinese export policies, we find that Chinese export competition reduces aggregate product-level exports. Firm-level analysis further shows that Chinese competition leads to substantial price cuts to retain market shares, especially for homogeneous products. In addition, we also discover that firms respond to the increased level of Chinese export competition by dropping their marginal products. Taken together, these results highlight the importance of export competition with China for developed countries.
Keywords: F14; F15; F61; L25; 330; Trade flows; Export competition; Firm-level; Product mix; China